Application of eco-efficiency in a coal-burning power plant benefitting both the environment and citizens: Design of a 'city water heating' system. (1st March 2017) - Rodríguez, R.; Bello, V.G.; Díaz-Aguado, M.B.
Highlights: Proposal for a waste heat recovery system, 'city water heating' system, is introduced. Conditions for its implementation are defined. Two 'city water heating' systems are subjected to both technical and economic analysis. Benefits for inhabitants, mainly reduced costs, are described and evaluated. Benefits for the environment, mainly CO2 emissions reduction, are quantified. Abstract: In this work, the concept 'city water heating' is introduced. It consists in bringing a significant amount of residual thermal energy (waste heat) from a power plant to a city by means of heating the potable water supplied to this city. For this purpose (i) a great amount of the city water has to be supplied through a single aqueduct, (ii) the aqueduct has to pass near the power station, and (iii) the water supplied to the city has to be colder than the cooling circuit water in the power plant. The hot water generated in the power plant cooling circuit (which is usually dissipated in the cooling tower) is conducted through a pipe to a place near the aqueduct and, by means of a heat exchanger, part of the cooling water heat is then transferred to the colder potable water supplied to the city. This has the great advantage of using the existing city water network itself to transport the heat to the houses. Based on data from a coal power plant located in Asturias (Northern Spain), two city water heating systems of different sizes are described and analysed. The following advantages were found: (i) energy saving and cost reduction for inhabitants, (ii) reduction in global warming and (iii) CO2 emissions reduction.